2022
DOI: 10.1002/jgh3.12686
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic and inflammatory bowel disease from patients' perspective: A survey from COVID epicenter in India

Abstract: Background and Aim The COVID pandemic and countrywide lockdown has had significant impact on patients with inflammatory bowel disease (IBD), with delay in diagnosis, difficulty in access to healthcare and unavailability of drugs. We conducted a telephonic survey to assess this impact. Methods Out of 350, 302 participated in the survey. Demographic data, disease severity at the time of survey, extent of disease, details of therapy, and adherence were noted. A validated questionnaire addressing information sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Telemedicine was a pivotal component of disease management during periods of lockdown, and patients were reportedly broadly satisfied with the transition [ 14 , 18 20 ]. During the COVID-19 pandemic, surveys carried out among patients with IBD reported that access to remote health care delivery systems can help to reduce disease-related concerns and suggest that telemedicine could remain a viable approach to disease management in the post-pandemic era [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telemedicine was a pivotal component of disease management during periods of lockdown, and patients were reportedly broadly satisfied with the transition [ 14 , 18 20 ]. During the COVID-19 pandemic, surveys carried out among patients with IBD reported that access to remote health care delivery systems can help to reduce disease-related concerns and suggest that telemedicine could remain a viable approach to disease management in the post-pandemic era [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to consider that not all patients will be able to benefit from the telemedicine model. In India, for example, nearly 30% of patients with IBD were unable to contact their health care provider by any means during the pandemic [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, social media platforms, television, and public health organization were cited as the main source of information. 12 , 13 , 18 , 23 This is also a consequence of the ease of access to treating physicians in Lebanon, with specialized care being readily available. Furthermore, these numbers highlight the trust that patients have in their gastroenterologist and the importance of that relationship, as it is the main source of relief and information.…”
Section: Discussionmentioning
confidence: 99%
“…11 Several studies have evaluated their perceptions regarding the outbreak in different countries. 5,[12][13][14][15][16][17][18][19][20] In this paper, we aim to evaluate IBD patients' perceptions and behaviors regarding the SARS-Cov-2 pandemic for the first time in Lebanon.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in an Indian survey, patients reported similar fears aimed at patients in remission in most or all-controlled clinical activities in which telemedicine methods had also been applied in most of the sample[ 24 ]. The authors reported reduced involuntary adherence (due to the unavailability of medication, financial constraints, and difficulty in reaching dedicated health facilities) with increased disease activity.…”
Section: Telemedicine: General Considerationsmentioning
confidence: 99%